Tradução das Diretrizes Curriculares Nacionais dos cursos de Medicina de 2001: análise do projeto pedagógico das universidades federais da região sudeste do Brasil - Arruda, Fernando Teles de (Universidade Federal de São Carlos, 2015)
The numerous changes in health care, is creating the need for revaluations and adjustments in vocational training policies. The health graduation, particularly medical training, has been challenged in this regard. In Brazil, the National Curriculum Guidelines, adopted in 2001 to guide the Pedagogical Project Course (PPC) health degree, are considered a major milestone in training, promoting the fight against health conditions of the population, expressed in health needs through a critical and reflective formation. Fourteen years after the publication of the DCN- 2001, the goal of this research was to analyze the translation of these guidelines in PPC's. the medical graduation projects of Federal Institutions in Southeastern Brazil were analyzed. The sample was composed of 12 institutions, after applying the inclusion and exclusion criteria. For the analysis of PPC's was built / validated an evaluation matrix. two axes were analyzed (i) curriculum and (ii) professional profile, according to the constituent elements of DCN. The analysis of PPC's identified the category "general profile egress" as the one closest to the Policy and Health Management category as the more distanced. The simple publication of the guidelines, as well as its translation in PPC's do not guarantee their applicability, but are an important indicator of educational Instituição. This research points to the need to create the PPC's discussion environments, stimulating sharing experiences, achievements and challenges, respecting the uniqueness of each institution, but stimulating the advancement towards the guidelines.
Keywords: Educação em saúde; Educação médica; Currículo; Educação de graduação em medicina; Health Education; Curriculum; Education, Medical, Undergraduate; CIENCIAS DA SAUDE::MEDICINA